PENDAMPINGAN ANAK USIA 6-12 TAHUN UNTUK MENINGKATKAN LITERASI DASAR PADA MASA PANDEMI DI RT05 RW17 WANASARI BEKASI - Anti Tri Octaviani; Musyaffa Amin Ash Shabah; Yoyo Hambali (Universitas Islam 45 Bekasi, 2022)
Learning at home is not effective so it has an impact on children's low motivation, including basic literacy activities. To overcome this, assistance was carried out in basic literacy activities for children aged 6-12 years in learning at home during the Covid-19 pandemic to increase motivation and help students with learning difficulties in studying at home. In addition, this mentoring activity can help parents in conducting targeted and structured home learning coaching. Assistance in basic literacy activities during the COVID-19 pandemic for children aged 6-12 years in RT 05 RW 17 can increase motivation and help with learning difficulties at home for children aged 6-12 years in RT 05 RW 17. This can be seen from the enthusiasm, enthusiasm, and seriousness of the children in the RT 05 RW 17 environment during the program activities.